Attack on Titan. 29 - Isayama, Hajime, 1986- (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2019)
As a Marleyan invasion dangles like a guillotine blade over the island of Paradis, allies have become enemies, and former friends are at each other<U+2019>s throats. The Yeagerists are in all-out revolt, fighting to dismantle military rule before the potential for world war explodes into certain doom. Meanwhile, deep in the forest, the sides<U+2019> most ruthless, fanatical killers are locked in single combat, but triumph is elusive where Titans are involved<U+2026>